Business process families using model-driven techniques. (16th September 2011) - Kulkarni, Vinay; Barat, Souvik
Traditionally, businesses have used IT systems as mechanical advantage for automating static a-priori-defined repetitive tasks. Increased business dynamics has placed greater demands of adaptation and agility on to IT systems. Service-oriented architecture is a step in this direction through separation of business process concerns from application functionality. There have been multiple attempts at improving adaptability of application services with varying degrees of success. But current business process modelling languages and execution platforms can at best support optimal point solutions that are not amenable for agile adaptation. Application services have benefited to some extent, from product-line architectures related to adaptation to a-priori known situations. We can apply the same idea to business processes. This paper presents an extension of essential BPMN meta model supporting business process families, and a set of adaptation operators are presented in this paper. We describe their realisation using model-driven techniques.